Combinatorial atmospheric pressure chemical vapour deposition (cAPCVD) of a mixed vanadium oxide and vanadium oxynitride thin film - Kafizas,A; Hyett,G; Parkin,IP (Journal of Materials Chemistry, 2009)
A novel combinatorial atmospheric pressure chemical vapour deposition (cAPCVD) technique was used to synthesise numerous vanadium oxide and vanadium oxynitride phases on a single film. This is the first example of cAPCVD having been used to synthesise a gradating mixed anion system. The film was characterised by X-ray diffraction (XRD) mapping, Raman, wavelength dispersive X-ray analysis (WDX) and X-ray photoelectron spectroscopy (XPS) analysis of positions along the film’s front edge allowed the chemical composition to be determined and correlated with XRD data. Film thicknesses were determined using side-on scanning electron microscopy (SEM). Functional property mapping of the optical transmittance/reflectance and electrical resistance allowed systematic investigation on the effects of oxygen content within a vanadium oxynitride film. cAPCVD used in conjunction with mapping analysis tools is a shortcut for identifying numerous, phases, compositions and properties and their relationships on a single film, and offers a rapid method for analysis of phase-space.